Interaction between glacial activity 2 and flood frequency in proglacial Lake Muzelle - Laurent Fouinat; Pierre Sabatier; Jérôme Poulenard; David Etienne; Anne-Lise Develle; Elise Doyen; Emmanuel Malet; Jean-Louis Reyss; Clotilde Sagot; Richard Bonet; Fabien Arnaud (PANGAEA, 2017)
Local glacial fluctuations and flood occurrences were investigated in the sediment sequence of proglacial Lake Muzelle. Based on geochemical analysis and organic matter content established using loss on ignition and reflectance spectroscopy, we identified six periods of increased glacial activity over the last 1700 yr. Each is in accordance with records from reference glaciers in the Alps. A total of 255 graded layers were identified and interpreted as flood deposits. Most of these occurred during glacial advances such as the Little Ice Age period and exhibit thicker deposits characterized by an increase in the fine grain-size fraction. Fine sediment produced by glacial activity is transported to the proglacial lake during heavy rainfall events. The excess of glacial flour during these periods seems to increase the watershed extquotesingles tendency to produce flood deposits in the lake sediment, suggesting a strong influence of the glacier on flood reconstruction records. Thus, both flood frequency and intensity, which is estimated based on layer thickness as a proxy, cannot be used in reconstruction of past extreme events because of their variability. There is a need to take into account changes in sediment supply in proglacial areas that could preclude satisfactory interpretation of floods in terms of past climate variability.
Supplement to: Fouinat, L et al. (2017): One thousand seven hundred years of interaction between glacial activity and flood frequency in proglacial Lake Muzelle (western French Alps). Quaternary Research, https://doi.org/10.1017/qua.2017.18